PEMAHAMAN SISWA MADRASAH ALIYAH TERHADAP MODERASI, RADIKALISME, DAN INTOLERANSI DI SOLO RAYA: CONTENT ANALYSIS ESAI PESERTA PELATIHAN LITERASI MODERASI - Hamdan Magribi; Taufiq Wijaya; Muhammad Baha Uddin (UIN Raden Mas Said Surakarta, 2026)
Understanding religion based on moderation is becoming increasingly important amidst the onslaught of radicalism and fundamentalism in Indonesia. This study aims to describe the implementation of the values ​​of moderation in life through moderation-based literacy among students in Solo Raya. With a focus on essay writing training, this study aims to instill awareness and moderate attitudes as a response to the increasing cases of intolerance in the educational environment. The method used in this study is descriptive qualitative. The study was conducted at Madrasah Aliyah Al Muayyad Surakarta with training participants from students throughout Solo Raya. The results of the study showed that moderation-based literacy activities play a role in honing awareness of moderation by providing students with an in-depth understanding of the importance of a moderate attitude in dealing with diversity, so as to reduce the potential for intolerance-based conflict. In addition, this training is also effective in improving literacy skills, essay writing becomes a strategic means to train critical thinking skills, express ideas in writing, and understand religious moderation in real contexts.